Multi-strain probiotic formula modulates expression of β-defensin-2, β-defensin-3, and TLR-4 in male rats with apical periodontitis - Cosme-Silva, Leopoldo; Dal-Fabbro, Renan; de Lima Pontes, Fernanda; Capalbo, Leticia Cabrera; Ervolino, Edilson [UNESP]; Cintra, Luciano Tavares Angelo [UNESP]; Segura-Egea, Juan José; Gomes-Filho, João Eduardo [UNESP] (Elsevier, 2025)
Objective: Evaluate whether a multi-strain probiotic formula affects blood parameters (hematologic, calcium, and phosphorus levels) and alters the expression of β-defensin-2, β-defensin-3, and toll-like receptor 4 in male rats with induced apical periodontitis (AP). Design: Wistar rats were divided into two groups (n = 8 each): (1) rats with AP on a regular diet (Control) and (2) rats with AP on a regular diet supplemented with the multi-strain probiotic GNC Probiotic Complex (GCP) at one billion CFU. AP was induced by exposing the dental pulp of the first molars to the oral environment. GCP was administered daily via gavage for 30 days during AP development. After 30 days, animals were anesthetized, a cardiac puncture was performed, and 5 mL of blood was collected for hematologic, calcium, and phosphorus analysis. Animals were then euthanized, and mandibles were removed for histological and immunochemical analysis of β-defensin-2, β-defensin-3, and toll-like receptor 4. Statistical analyses used Mann–Whitney U and Student's t-tests, with significance at P < 0.05. Results: No significant differences were observed in blood parameters between the Control and GCP groups (P > 0.05). In AP, the Control group showed more intense inflammatory infiltrates and higher median severity scores than the GCP group (P < 0.05). Immunoreactivity levels for β-defensin-2, β-defensin-3, and toll-like receptor 4 were significantly increased in the GCP group (P < 0.05). Conclusion: Probiotic complex reduces inflammation and enhances immunolabeling of β-defensin-2, β-defensin-3, and toll-like receptor 4 in AP.
Keywords: Apical periodontitis; Inflammatory infiltrate; Probiotics